2005
DOI: 10.1038/sj.jcbfm.9600082
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT1 Receptor Blockade Abolishes Brain Microvascular Inflammation and Heat Shock Protein Responses in Hypertensive Rats

Abstract: Endothelial dysfunction and inflammation enhance vulnerability to hypertensive brain damage. To explore the participation of Angiotensin II (Ang II) in the mechanism of vulnerability to cerebral ischemia during hypertension, we examined the expression of inflammatory factors and the heat shock protein (HSP) response in cerebral microvessels from spontaneously hypertensive rats and their normotensive controls, Wistar Kyoto rats. We treated animals with vehicle or the Ang II AT 1 receptor antagonist candesartan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 36 publications
(67 reference statements)
9
108
0
2
Order By: Relevance
“…We did not measure the activity or levels of components of the RAAS in our rats, and it is possible that the system is upregulated in this model of renal disease. For example, it has been reported that expression of AT1R is increased in the inflamed renal parenchyma (41)(42)(43)(44)(45). Therefore, it is reasonable to speculate that higher dosages of candesartan were needed to block completely the increased numbers of AT1R in the diseased SHR kidney.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure the activity or levels of components of the RAAS in our rats, and it is possible that the system is upregulated in this model of renal disease. For example, it has been reported that expression of AT1R is increased in the inflamed renal parenchyma (41)(42)(43)(44)(45). Therefore, it is reasonable to speculate that higher dosages of candesartan were needed to block completely the increased numbers of AT1R in the diseased SHR kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Brain microvessels were isolated and characterized as described previously (19). A detailed description of these techniques is also provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Given the high prevalence of vascular complications in DM (18), severe pathological changes in the cerebral vasculature could be detected in APP + -ob/ob mice and potentially impact on cognitive function. Thus, we isolated the microvessels from mouse brains (19) and immunostained them with anti-Aβ40 antibody. At 12 months of age, faint amyloid deposits had appeared in blood vessels in the brain of APP + mice (Fig.…”
mentioning
confidence: 99%
“…Interestingly, there is growing evidence that SH rats and hypertensive human patients share common pathophysiological characteristics of neurogenic hypertension including vascular inflammation and cerebral microvessel alterations, which are pathognomonic for SVD. [10][11][12] Recent clinical and preclinical investigations revealed that hypertension activates a plethora of inflammatory cascades including chronic activation of microglia, 12 thereby constituting a specific prerequisite for the immunologic facet of cerebral stroke. We hence considered SH rats to be a promising animal model for studying postischemic inflammation and immunodepression closely correlated to pathophysiological conditions existing in human stroke patients.…”
Section: Introductionmentioning
confidence: 99%